CORRELATION FOR SOLUTION GAS -OIL RATIO OF IRAQI OILS AT PRESSURES BELOW THE BUBBLE POINT PRESSURE - F. Hassan, Omar (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
The solution gas-oil ratio is an important measurement in reservoir engineering calculations. The correlations are used when experimental PVT data from particular field are missing. Additional advantages of the correlations are saving of cost and time. This paper proposes a correlation to calculate the solution gas -oil ratio at pressures below bubble point pressure. It was obtained by multiple linear regression analysis of PVT data collected from many Iraqi fields. In this study, the solution gas-oil ratio was taken as a function of bubble point pressure, stock tank oil gravity, reservoir pressure, reservoir temperature and relative gas density. The construction of the new correlation is depending on thirty seven PVT reports that were collected from Iraqi fields. Statistical and graphical tools have been used to check the performance of the correlation. Correlation performance was also compared with previous published correlations. The values of solution gas - oil ratio that were calculated from the new correlation have high accuracy when they were compared with the original laboratory data. Also, the results of the new correlation show high precision when compared with Standing [1], Vasquez and Beggs [2], Glaso [3], Al-Marhoun [4], Petrosky and Farshad [5], Kartoatmodjo and Schmidt [6], Velarde, Blasingame and McCain [7] and Mazandarani and Asghari [8] correlations.